Direct and indirect associations between mental health and motivational indicators with physical activity among Lithuanian adolescents - Mieziene, Brigita; Venckunas, Tomas; Emeljanovas, Arunas; Trinkuniene, Laima; Zaicenkoviene, Kristina; Vizbaraite, Daiva (Frontiers in Psychology, 2025)
BackgroundConsidering the low engagement of contemporary adolescents in physical activity (PA), apparently, PA still has a low priority for adolescents, who are the only ones making decisions and performing behavior. So, analysis of more proximal factors that lay on the personal and interpersonal levels as well as psychological mechanisms forming PA behavior is important.MethodsThe population-based cross-sectional study included 4,924 5th to 12th-grade school students. Among them, 50.9% were girls. The mean age of study participants varied from 11 to 19 years [mean 14.08 (2.21)]. Moderate-to-vigorous physical activity was measured by four items out of the IPAQ-SF questionnaire. Psychological well-being was assessed using The World Health Organization Five Well-Being Index (WHO-5) 5-item questionnaire. Psychological distress has been assessed by Kessler’s six-item scale. Social support in terms of family and friends social support has been assessed by a 13-item subscale of Sallis’ Support for Exercise Survey. Body mass index (BMI) was calculated by dividing body mass (kg) by height-squared (m2).ResultsHigher motivation for MVPA was predicted by higher family (β = 0.653) but not friends‘support and both mental health indicators – higher psychological well-being (β = 0.049) and lower psychological distress (β = −0.078) were linked to higher motivation for physical activity, regardless the covariates. Higher motivation (β = 0.137), greater psychological well-being (β = 0.580) with the greatest magnitude, and lower psychological distress (β = −0.293) contributed to the greater MVPA.ConclusionFamily but not friends’ support for physical activity, greater psychological well-being, and lower psychological distress have direct and indirect effects on greater moderate-to-vigorous physical activity in adolescents.